Zinc oxide grounds in 19th and 20th century oil paintings and their role in picture degradation processes - Elena Pratali (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
When zinc oxide is the main constituent of a ground layer, its stiffness and brittle behavior could affect the whole paint system, producing damages to upper pigmented layers. Zinc white and white lead paint samples have been prepared and artificially aged. Visual data have been collected, and FTIR spectroscopy has proved effective in confirming the formation of zinc carboxylates. Guidelines for conservation treatments were drawn on both technical procedures and choice of materials.